Intemporal Capital Assets Pricing Model Sebagai Prediktor Return Portofolio Saham - Amaroh, Siti (Jurnal Ilmu Ekonomi ASET, 2009)
This study has purpose to examine Capital Assets Pricing Model (CAPM) andFama-French Model for firms listed on Indonesia Stock Exchange for the period 1992-2000both in up market and down market using all nonfinancial and banking firms. The resultshows that portfolio returns are affected by market factor, excess return on portfolio constructedby size (Small Minus Big, SMB), and excess return on portfolio constructed by book-to-marketratio (High Minus Low, HML). Market factor positively affects portfolio return in all monthlytest and in down market, but not significant in up market. Return differences of portfolioconstructed by size is also positively affects on small stock portfolio return for all monthlytests and down market. Return differences of portfolio constructed by book-to-market ratio ispositively affects on portfolio return for all monthly test both in up and down market.Keywords : Capital Assets Pricing Model, Small Minus Big, High Minus Low.